2021
DOI: 10.1515/med-2021-0361
|View full text |Cite
|
Sign up to set email alerts
|

No significant benefit of moderate-dose vitamin C on severe COVID-19 cases

Abstract: There is no specific drug for coronavirus disease 2019 (COVID-19). We aimed to investigate the possible clinical efficacy of moderate-dose vitamin C infusion among inpatients with severe COVID-19. Data of 397 adult patients with severe COVID-19 admitted to a designated clinical center of Wuhan Union Hospital (China) between February 13 and February 29, 2020, were collected. Besides standard therapies, patients were treated with vitamin C (2–4 g/day) or not. The primary outcome was all-cause death. Secondary ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…However, we attempted to address this limitation by performing a sensitivity analysis of the 5 randomized controlled trials. Lastly, the included studies (23)(24)(25)(26)(27)(28)(29)(30)(31)(32) in the meta-analysis did not consistently report on adverse events potentially related to administration of vitamin C, such as oxalate nephropathy, hypernatremia and glucometer error. Nevertheless, relevant evidence before the pandemic indicated that high-dose vitamin C may be relatively safe (36).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, we attempted to address this limitation by performing a sensitivity analysis of the 5 randomized controlled trials. Lastly, the included studies (23)(24)(25)(26)(27)(28)(29)(30)(31)(32) in the meta-analysis did not consistently report on adverse events potentially related to administration of vitamin C, such as oxalate nephropathy, hypernatremia and glucometer error. Nevertheless, relevant evidence before the pandemic indicated that high-dose vitamin C may be relatively safe (36).…”
Section: Discussionmentioning
confidence: 99%
“…2). In the sensitivity analysis of studies with low risk of bias (23,25,(28)(29)(30)32), mortality was 25.1% in the vitamin C group and 32.2% in the control group (RR 1.13, 95% CI 0.59-2.16; p = 0.72; six studies; 1,344 patients; 410 deaths; Supplementary Figure 1); while, in the sensitivity analysis of randomized controlled trials (25,27,29,31,32), the relevant numbers were 10.5 and 17.2%, respectively (RR 0.66, 95% CI 0.39-1.14; p = 0.14; five studies; 346 patients; 48 deaths; Supplementary Figure 2).…”
Section: Observational Studymentioning
confidence: 99%
See 3 more Smart Citations